Association between age at first sexual intercourse and knowledge, attitudes and practices regarding reproductive health and unplanned pregnancy: a cross-sectional study. (June 2016) - Shu, C.; Fu, A.; Lu, J.; Yin, M.; Chen, Y.; Qin, T.; Shang, X.; Wang, X.; Zhang, M.; Xiong, C.; Yin, P.
Abstract: Background: Age at first sexual intercourse (AFSI) is decreasing among adolescents in developed nations. An early sexual debut has been associated, to some extent, with multiple sexual partners, infrequent use of condoms, unplanned pregnancy, unsafe abortion, and sexually transmitted disease and human immunodeficiency virus infection. Unplanned pregnancy among adolescents has both physical and social adverse effects. Methods: In total, 78, 400 self-administered anonymous questionnaires were distributed to college students in seven cities in China to determine the age at which Chinese college students first engage in sexual activity, and the association between AFSI and knowledge, attitudes and practices (KAP) regarding reproductive health and unplanned pregnancy. Results: Approximately 10, 164 students reported that they were sexually active, and most reported that they had engaged in sexual intercourse for the first time during college. The average AFSI was 20.14 [standard deviation (SD) 2.98] years, and the average AFSI by gender was 19.97 (SD 2.97) years for males and 20.41 (SD 2.97) years for females. The unplanned pregnancy rate among the participants was 34.03%. Participants lacked knowledge about contraception and reproductive health, although most believed that it is necessary to have this knowledge. Participants' attitudes towards premarital sex were varied. Factors that were found to be associated with unplanned pregnancy were AFSI, contraceptive methods used for first sexual act, and whether contraceptive methods were used for every sexual act. Conclusions: The college period is a key time for Chinese students in terms of becoming sexually active. As such, comprehensive and informative reproductive health education should be provided before and during the college period. Furthermore, reproductive health education should include appropriate sexual morality education and comprehensive sex education. Gender traits and needs should be considered in sex education. Highlights: This paper indicated that college period is a key period for Chinese college students engaged in their first sex. The factors related to unplanned pregnancy were age and contraceptives used at first sex and contraceptive habits. These results indicate that we should provide comprehensive and informative reproductive health education. Reproductive health education should include both appropriate sexual morality education and comprehensive sex education.